Marcas e lugares: um estudo sobre marcas turísticas no Rio de Janeiro - Caversan, Adriana Lima [UNESP]; Silva, José Carlos Plácido da [UNESP]; Menezes, Marizilda Santos [UNESP]; Paschoarelli, Luis Carlos [UNESP] (My University, 2014)
This paper, through a literature review, demonstrates the importance of the use of brands by men, initially as a form of expression and communication. History has shown that the visual language and the use of images in the form of the brands, proved a very efficient and direct interpretation, with accuracy to what it represents, setting the brand as a financially valued member. The paper deals with analysis of the Spanish example that argues the way that touristic points has been used to represent places in the whole world; then, at the same time, it measures the case of the Brazilian city of Rio de Janeiro where brands are created for special events and there is not a representative tourist brand to this town; But when analyzing the places in the city, symbols like The Copacabana Promenade has a strong presence in the collective imagination, that's the reason why it has been used as an element of strong local identity and in the Industrial Design.

Este artigo, por meio de revisão bibliográfica, demonstra a importância da utilização de marcas pelos homens, inicialmente como uma forma de expressão e comunicação. A história demonstra que a linguagem visual e o uso de imagens, na forma de marcas, mostrou-se um meio muito eficiente e de direta interpretação, apresentando confiança àquilo que ela representa, firmando a marca como um elemento valorizado financeiramente. O artigo trata, por meio de análises, do exemplo espanhol que demonstra a maneira como as marcas turísticas vêm sendo utilizadas no mundo para representar lugares; depois, paralelamente, avalia o caso brasileiro da cidade do Rio de Janeiro onde as marcas são criadas para eventos específicos e não há uma marca turística representativa dessa cidade turística; porém, ao analisar os lugares da cidade, é trazida à tona a forte representação de que símbolos, como o Calçadão de Copacabana, têm no imaginário coletivo, sendo este um elemento de forte identificação local e usado inclusive no Design de produtos.
Keywords: Brands; Symbology; Tourism; Representation; Marcas; Simbologia; Turismo; Representação